Biogas Generation from Liquid Waste of Tapioca Starch Processing via a Single Stage of Anaerobic Digestion and Microbial Electrolysis Cell: The Effect of Trace Element Iron Addition - Bianca Amartya Prabowo; Iqbal Syaichurrozi; Achmad Faizal Ibrahim; Farhan Fadlurohman Tsaqif; Muhamad Ariel Satria; Muhammad Doni Fachriza; Alia Badra Pitaloka (Politeknik Negeri Malang, 2026)
The industries of tapioca starch processing result in a substantial amount of liquid waste (TSPW), characterized by high concentrations of organic compounds. Because of its chemical oxygen demand (COD), the tapioca wastewater is not permitted to be thrown away directly into the surrounding. The new method of combination of anaerobic digestion (AD) and microbial electrolysis cell (MEC) is proposed to be applied to convert COD in the tapioca wastewater to biogas. The main objective of this study is to examine the impact of FeCl3 addition on MEC-AD performance in converting tapioca wastewater to biogas. The FeCl3 dose varied to 0 (control), 200, 400, 600, and 800 mg/L. The results revealed that FeCl3 doses of 0, 200, 400, 600, and 800 mg/L generated total biogas yields of 197.1, 276.11, 261.2, 239.48, and 202.2 mL/g-CODadded, respectively. Then, the FeCl3 doses of 0, 200, 400, 600, and 800 mg/L achieved COD removals of 62, 71, 66, 65, and 63%, respectively. Furthermore, the FeCl3 doses of 0, 200, 400, 600, and 800 mg/L had total solid (TS) removals of 33, 51, 48, 35, and 27%, respectively. Hence, the optimal FeCl3 dose in MEC-AD of tapioca wastewater is 200 mg/L. Through the modified Gompertz model, the FeCl3 dose of 200 mg/L had the highest value (275.94 mL/g-CODadded) and the highest value (186.61 mL/g-CODadded/day).